Latest improvements in CIEF: from proteins to microorganisms - Šalplachta, Jiří; Kubesová, Anna; Horká, Marie (Proteomics, 2012)
In recent years, characterization and identification of microorganisms has become very important in different fields of human activity. Conventional laboratory methods are time consuming, laborious, and they may provide both false positive or negative results, especially for closely related microorganisms. On that account, new methods for fast and reliable microbial characterization are of great interest. In particular, capillary electrophoretic techniques have a great potential for characterization of microorganisms due to their unique surface properties. Cell surface proteins play a key role in this respect. Since CIEF represents one of the most efficient techniques for protein separation, it was consequently applied to the analysis of microbial cells. This review describes, after a brief introduction to CIEF of proteins, recent developments in CIEF of diverse microorganisms (viruses, bacteria, yeasts, and fungi). Possible application schemes in human and veterinary medicine as well as in plant protection and in biosecurity are outlined.
Keywords: viry; Fungi; proteiny; Isoelectric Focusing; Bacteria; houby; Animals; lidé; Proteins; Viruses; Humans; isoelektrická fokusace; zvířata